2019
DOI: 10.18805/ijar.b-1165
|View full text |Cite
|
Sign up to set email alerts
|

Reference Values for Selected Blood Parameters in Rabbits: Effects of Age and Physiological Status

Abstract: Rabbit is widely used as an experimental animal model in infectious and non-infectious diseases. The haematologic data can be helpful in evaluating the health status of animals over time. The aim of this study was to determine the levels of red blood cells (RBC), white blood cells (WBC) and differential leukocyte counts in 5 nulliparous and 5 multiparous females, i.e. in young and older animals, at mating and at delivery. The values of RBC did not change with age, but WBC and lymphocytes decreased with age, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Lymphoid stem cells differentiating in bone marrow develop to T cells primarily in thymus and spleen. There was a positive correlation between the number of lymphocytes and the immunity of the body (Dar et al, 2018, Argente et al, 2019. With the aging of body, The amount of T cells declines and the immune decline (Chason et al, 2018).The number and subpopulations of T cells in peripheral blood also change which results in the decrease of CD 3 + 0CD 4 + and CD 8 + T cells (Coiffard et al, 2018, Ilienko et al, 2017, Sanderson and Simon, 2017.…”
Section: G0/g1 + S + G2mmentioning
confidence: 99%
“…Lymphoid stem cells differentiating in bone marrow develop to T cells primarily in thymus and spleen. There was a positive correlation between the number of lymphocytes and the immunity of the body (Dar et al, 2018, Argente et al, 2019. With the aging of body, The amount of T cells declines and the immune decline (Chason et al, 2018).The number and subpopulations of T cells in peripheral blood also change which results in the decrease of CD 3 + 0CD 4 + and CD 8 + T cells (Coiffard et al, 2018, Ilienko et al, 2017, Sanderson and Simon, 2017.…”
Section: G0/g1 + S + G2mmentioning
confidence: 99%
“…Hematological techniques are the most common methods to detect stress and pollutant induced physiological changes. Animal studies have shown that aluminum is implicated as a contributing factor and an etiologic agent in anemia (Adham et al, 2011;Geyikoglu et al, 2013;Muayad et al, 2018;Argente et al, 2019). Effects of aluminum on liver and kidney functions in rat were evidenced by the increased serum levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT) and creatinine (Geyikoglu et al, 2013;Balgoon, 2019).…”
Section: Introductionmentioning
confidence: 99%